Development of superhydrophobic surface on mild steel by a facile approach and analyzing its self-cleaning and anti-freezing properties - Bala Manikandan Cheirmakani; Karthikeyan M; Balamurugan S; Jeen Robert RB (Results in Surfaces and Interfaces, 2024)
Superhydrophobic surfaces are currently a subject of great interest because of their tremendous applications. This study offers greater insight into the self-cleaning ability and anti-icing behavior of the superhydrophobic mild steel and finds application in aircraft and marine systems. Superhydrophobic surfaces were developed on the mild steel surface by improving the roughness and reducing the energy on the surface. Mild steel was chemically etched with HCL solution for 10 min to improve the roughness. After etching, the surfaces were immersed in stearic acid solution for 3 h by solution immersion method to introduce low surface energy. The resultant surfaces have a combination of nano and micro-roughness. The roughness of the samples was measured with the aid of surface roughness tester. The roughness of the prepared surface is 4.213 μm. The microstructure of the as-prepared surface was characterized by a scanning electron microscope. The surfaces have changed to be pine-cone-like structure. The pinecone-like hierarchical structures can generate numerous grooves in which the air can be trapped which lead to a larger contact angle. The contact angle was measured by using a goniometer setup. The obtained contact angle of the surface is as high as 154° with a lower contact angle hysteresis. The surfaces were tested for self-cleaning and ice-delaying properties. The as-prepared superhydrophobic surfaces can self-clean the surface from dirt/dust while the water droplets roll over the surface. A freezing delay time of 392 s was achieved on the surfaces. The prepared surfaces possess better self-cleaning and ice-delaying properties.